PYK2 in osteoclasts is an adhesion kinase, localized in the sealing zone, activated by ligation of alpha(v)beta3 integrin, and phosphorylated by src kinase. - Duong, L T (1998)
Osteoclast activation is initiated by adhesion to the bone surface, followed by cytoskeletal rearrangement, the formation of the sealing zone, and a polarized ruffled membrane. This study shows that PYK2/CAKbeta/RAFTK, a cytoplasmic kinase related to the focal adhesion kinase, is highly expressed in rat osteoclasts in vivo. Using murine osteoclast-like cells (OCLs) or their mononuclear precursors (pOCs), generated in a coculture of bone marrow and osteoblastic MB1.8 cells, we show: (a) tyrosine phosphorylation of PYK2 upon ligation of beta3 integrins or adhesion of pOCs to serum, vitronectin, osteopontin, or fibronectin but not to laminin or collagen; (b) coimmunoprecipitation of PYK2 and c-Src from OCLs; (c) PYK2 binding to the SH2 domains of Src; (d) marked reduction in tyrosine phosphorylation and kinase activity of PYK2 in OCLs derived from Src (-/-) mice, which do not form actin rings and do not resorb bone; (e) PYK2 phosphorylation by exogeneous c-Src; (f) translocation of PYK2 to the Triton X-100 insoluble cytoskeletal fraction upon adhesion; (g) localization of PYK2 in podosomes and the ring-like structures in OCLs plated on glass and in the sealing zone in OCLs plated on bone; and (h) activation of PYK2, in the presence of MB1.8 cells, parallels the formation of sealing zones and pit resorption in vitro and is reduced by echistatin or calcitonin and cytochalasin D. Taken together, these findings suggest that Src-dependent tyrosine phosphorylation of PYK2 is involved in the adhesion-induced formation of the sealing zone, required for osteoclastic bone resorption.